Metaevaluation and its Standards - Sakineh Sabsevari (Kerman University of Medical Sciences, 2006)
Background: Metaevaluation is a process that design collect and use information for judging about evaluation and generally determine weak and strong Joint Committee on Standards for Educational Evaluation believed that quality of evaluation is depended on utility feasibility propriety and accuracy A utility standard means that evaluation meets informational needs for users Feasibility standards are intended to ensure that an evaluation will be realistic prudent diplomatic and frugal Propriety standards are for doing evaluation at legal and ethical manner with considering welfare of those involved in evaluation and as well as those affected by its results Finally accuracy standards collect adequate information about the features that determine worth or merit of the program being evaluated Conclusion: Metaevaluation try to find a proper method for doing evaluationsIt can include program student project product system institute theory personnel evaluation